Need Analysis on Therapeutic Communication of Palliative Nursing in English for Specific Purposes (ESP) - Husna, Arina Hafadhotul; Hindriyastuti, Sri (Universitas Nusantara PGRI Kediri, 2023)
English for Specific Purposes (ESP) is designed to meet students' specific needs. It deals with a need analysis. It is crucial to conduct a need analysis before designing the materials and syllabus. The material learned by students in the Academic process should correlate to the student’s needs in the professional world/work world. This research is a Research and Development (R&D) which used ADDIE Model. It explored the required skills and difficulties encountered by the students in learning English, analyzed the learning materials topic that supports the profession, and the components of communicative competence need on therapeutic communication materials of palliative nursing. The data were collected through questionnaires and interviews. There were 30 nursing students and 2 nursing lecturers. The questionnaires were distributed to students to explore their needs, while the interview was used to support data from the questionnaire. The findings indicated that since it focuses on therapeutic communication of palliative nursing, speaking skills need to train more. This skill is important as well as listening, reading, and writing. It is interconnected and can not stand alone. All of them need to be mastered by students. The material content taught needs to focus on the cases of palliative nursing, and it must follow the steps of therapeutic communication techniques and strategies applied in daily nursing intervention procedures. So ESP nursing course will support the institution in producing qualified graduates who are competent and skilled in their profession, capable to communicate in both English and Indonesian, competing, and being ready to work in the international world.